Comprehensive energy modeling methodology for battery electric buses. (15th September 2020) - Basma, Hussein; Mansour, Charbel; Haddad, Marc; Nemer, Maroun; Stabat, Pascal
Abstract: With the announced plans to ban diesel in major European cities from 2025, battery-powered electric buses (BEB) are attracting attention to replace diesel fleets, given their zero tailpipe emissions. However, their large-scale deployment faces several challenges, namely the limited driving range (DR) and the need for adequate charging infrastructure. The limited DR is due to the lower battery specific energy compared to oil-based fuels. Also, the use of electric auxiliaries, especially, air conditioning, reduces the DR further. The DR problem could be resolved either by increasing the battery capacity, which increases the bus cost or by rightsizing the battery alongside an adequate charging strategy to avoid schedule disruption. Therefore, this paper presents a comprehensive energy modeling of a BEB using Dymola, encompassing the different energy systems encountered in BEB. The proposed model serves as a platform to evaluate the bus energy needs during its service to properly size the battery. A powertrain model is presented to emulate the propulsion load. Then, a cabin model alongside a heating ventilating and air conditioning system are developed emulating the thermal load. Finally, auxiliaries necessary for the bus operation are modeled. The energy consumption of each system is assessed under several operating conditions. Graphical abstract: Image 1 Highlights: Study proposes a modeling methodology to assess battery electric buses energy consumption. Assesses the impact of different driving and weather conditions and passengers load on the energy consumption. Model serves as a platform to evaluate battery electric buses energy needs to properly size the battery. Cabin thermal needs and auxiliaries reduce driving range by more than 50% under extreme weather and driving conditions.